The acquisition of legitimacy for civilian policing: a case study of pedophile hunting groups - Ireland, Leanna (Crime, law and social change, 2023)
The state has encouraged civilians to take control of their own security through partnership and self-governance. Resultantly, civilians involved in the provision of security are attempting to obtain legitimacy for their civilian policing efforts. To investigate the acquisition of legitimacy for civilian policing, this article analyses comments (n = 1036) from an e-petition launched by a pedophile hunting group seeking legality for their enforcement operations. Because the e-petition eventually became dominated by QAnon conspiracy followers, the article also examines the QAnon movement in relation to civilian policing. The findings provide insight into justifications for the legality of civilian policing that are supplied by the general public in their efforts to support such groups, the process of de-legitimatization of the policing capabilities of the state, and the risks of what I call legitimacy tethering, linking civilian policing initiatives to radical groups such as QAnon.